Quality control of semen processing in boar studs: A Brazilian scenario - Janaina Colecha Rocha; Emanoelle Regina Rosa; Monike Quirino; Mariana Groke Marques; Paulo Eduardo Bennemann; Arlei Coldebella; Lucio Pereira Rauber; Elizabeth Schwegler; Fabiana Moreira; Vanessa Peripolli; Thomaz Lucia Junior; Ivan Bianchi (Scientia Agricola, 2024)
ABSTRACT Artificial insemination success in swine is mainly associated with semen dose quality. Thus, this study compared quality control parameters in 11 Brazilian boar studs after applying audit services for 24 months (1,650 boars). An extensive checklist was applied in each audit, registering ‘compliance’ or ‘noncompliance’ for 75 items. Semen doses produced were analyzed as regards volume and sperm concentration, and microbiological analyses were conducted for semen and water samples collected at distinct production stages. On average, boar studs produced 112.9 semen doses per boar per month, and the odds of raw semen contamination increased when boars were inadequately housed and doses were collected under increased temperatures, with no anti-slip rubber mat or after a poor prepuce cleaning (p < 0.05). Collection from boars with locomotor problems and no regular change of reverse osmosis filters increased the contamination odds in semen doses produced and stored at the stud (p < 0.05). As regards the water submitted to the osmosis reverse process, contamination odds increased as a result of deficient cleaning and disinfection of the purification equipment (p < 0.05). Risk factors for reduced sperm motility (< 70 %) were: no anti-slip rubber mat for semen collection, no cleaning program for automatic feeding system (drops) and bins, and inadequate intervals between semen collections (≤ 2 days or > 7 days; p < 0.05). Two boar studs had the best results for compliance with the checklist items. Constant monitoring, appropriate hygiene of facilities and equipment, and periodical staff training are highlighted as non-negotiable points for boar semen dose quality.